Gene Therapy With Regulatory T Cells: A Beneficial Alliance - Biswas, Moanaro; Kumar, Sandeep R. P.; Terhorst, Cox; Herzog, Roland W. (Frontiers in Immunology, 2018)
Gene therapy aims to replace a defective or deficient protein at therapeutic or curative levels. Improved vector designs have enhanced safety, efficacy and delivery, with potential for lasting treatment. However, innate and adaptive immune responses to the viral vector and transgene product remain obstacles to the establishment of therapeutic efficacy. It is widely accepted that endogenous regulatory T cells (Tregs) are critical for tolerance induction to the transgene product and in some cases, the viral vector. There are two basic strategies to harness the suppressive ability of Tregs: in vivo induction of adaptive Tregs specific to the introduced gene product, or concurrent administration of autologous, ex vivo expanded Tregs. The latter may be polyclonal or engineered to direct specificity to the therapeutic antigen. Recent clinical trials have advanced adoptive immunotherapy with Tregs for the treatment of autoimmune disease and in patients receiving cell transplants. Here, we highlight the potential benefit of combining gene therapy with Treg adoptive transfer to achieve sustained transgene expression. Furthermore, techniques to engineer antigen specific Treg cell populations, either through reprograming conventional CD4+ T cells or transferring T cell receptors with known specificity into polyclonal Tregs, are promising in pre-clinical studies. Thus, based upon these observations and the successful use of chimeric [IgG-based] antigen receptors (CARs) in antigen-specific effector T cells, different types of CAR Tregs could be added to the repertoire of inhibitory modalities to suppress immune responses to therapeutic cargos of gene therapy vectors. The diverse approaches to harness the ability of Tregs to suppress unwanted immune responses to gene therapy and their perspectives are reviewed in this article.